"A Very Photogenic Cat": Personhood, Social Status, and Online Cat Photo Sharing. (3rd May 2020) - Austin, Jessica; Irvine, Leslie
ABSTRACT: This study explores how domestic cats and their connections to humans are represented in a modern photo-sharing context through content analysis of Reddit, a popular social media website. By examining the photos that cat owners share online, as well as the language that accompanies the photos, we create an understanding of how images encourage the social construction of cats as beings who exhibit features of personhood. We collected photos and accompanying titles from the largest cat community on Reddit. We used value coding to examine attitudes toward cats in post titles and pattern coding to develop overarching themes. We used a similar approach for analyzing photos: we assigned each image one or more codes describing the cat, humans, and other relevant details. We then generated themes to describe the dataset overall. Individuals who contribute to the online community inform multispecies social theory through constructing their cats as persons embedded in relationships with humans, particularly in families, in many of the same ways as did personal photography from the early twenti- eth century. Cat owners impart personhood through attribution of thought, individuality, and emotion, as well as defining the cat's social space. They also conceive of cats as members of the family through expressions of caretaking, biographies, and mourning rituals. Through meaningful, intentional interactions, cats are widely constructed as persons who fulfill familial and social functions in many of the same ways as humans. Examination of the human– cat relationship and its social context may inspire higher esteem for cats, resulting in more compassionate treatment in policy circles and in society.